2005
DOI: 10.1176/appi.ajp.162.12.2315
|View full text |Cite
|
Sign up to set email alerts
|

Altered White Matter/Gray Matter Proportions in the Striatum of Patients With Schizophrenia: A Volumetric MRI Study

Abstract: The proportion of white matter to gray matter tissue volumes of the caudate, putamen, and nucleus accumbens is altered in medicated chronic schizophrenia patients, but the total volumes are unchanged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 36 publications
3
33
1
Order By: Relevance
“…Gray and white matter volumes of segmented striatal structures have been examined in the present subject material and we found evidence for an altered ratio of white to gray matter in patients compared with healthy control subjects although the total volumes were unchanged [Tamagaki et al, 2005]. In the present study, patients homozygous for the 270 C/T C allele displayed larger total caudate volumes than those carrying the C/T genotype.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…Gray and white matter volumes of segmented striatal structures have been examined in the present subject material and we found evidence for an altered ratio of white to gray matter in patients compared with healthy control subjects although the total volumes were unchanged [Tamagaki et al, 2005]. In the present study, patients homozygous for the 270 C/T C allele displayed larger total caudate volumes than those carrying the C/T genotype.…”
Section: Discussionsupporting
confidence: 53%
“…The direction of volume size in the patient group was not consistent with the one found in the healthy control subjects. In the previous study on striatal volumes, we found lower white to gray matter ratios in the striatum of patients with increased gray matter volumes of the putamen in the patients and corresponding reductions of the white matter of the caudate and the accumbens nuclei [Tamagaki et al, 2005]. In analogy with the previous reasoning, the BDNF À633 T/A polymorphism, or a gene variant in linkage disequilibrium with it, may be influential to gray matter putamen size and function and has a differential effect in schizophrenic patients compared with healthy control subjects.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Ten healthy control subjects also underwent MRI. The schizophrenic patients had reduced volumes of grey and white matter in the caudate nucleus compared to the healthy con-Okugawa/Nobuhara/Takase/Saito/ Yoshimura/Kinoshita Neuropsychobiology 2007;55: [43][44][45][46] 44 et al [2] reported that schizophrenic patients had a reduced white matter volume in the caudate nucleus compared to healthy subjects. An increased volume of the caudate nucleus was found in patients with first-episode schizophrenia [3] .…”
Section: Introductionmentioning
confidence: 99%